The Existence of Bekayat Tradition in Sembung Village, Narmada Subdistrict, West Lombok - Qirom, Syahrul; Permana, Beny; Subhan , Subhan (Gema Cendekia Institute, 2024)
Traditional arts often face challenges in evolving with the times. The processes of inheritance and preservation become common diction and challenges in maintaining the existence of traditional arts. This is one of the issues faced by the traditional art group Bekayat in Sembung Village, Narmada Subdistrict, West Lombok Regency. Observing such a reality of tradition, researching the existence of the Bekayat tradition becomes an interesting topic. The goal is to understand the reality of the Bekayat tradition through the analysis of its form, function, and inheritance process in maintaining its existence. A descriptive qualitative method is used to address the issues, with data collection techniques including observation, interviews, and documentation. To test the validity of the data, the researcher uses triangulation techniques. The results show that the existence of the Bekayat tradition in Sembung Village, Narmada Subdistrict, West Lombok Regency has weakened. Several factors contribute to the weakening existence of this tradition, namely: 1) Political factors. 2) Economic factors. 3) Regeneration factors.